2022
DOI: 10.3390/ijerph19042126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biochar on Rhizosphere Bacterial Diversity Restoration Following Chloropicrin Fumigation of Planted Soil

Abstract: Chloropicrin (CP) can effectively combat soil-borne diseases but has significant side effects on nontarget microorganisms. The rhizosphere microflora play a crucial role in promoting plant growth and protecting plants from infection by soil-borne pathogens. We conducted a laboratory pot experiment to evaluate the effect of CP on the rhizosphere soil bacterial flora and the effect of biochar amendments on the reconstruction of microbial communities. Our results show that CP fumigation and biochar additions prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…Biochar amendment increased the relative abundance of Micromonospora, which is known to have plant growth-promoting traits including nitrogen fixation and the inhibition of plant pathogens (Li et al, 2022); our results were in agreement with this study, for being the dominant genus in 30 mesh. Micromonospora not only presented higher relative abundance in biochar and BOF treatments compared with CK but also showed a strong positive correlation with AN, AP, and K. Bacillus spp.…”
Section: Discussionsupporting
confidence: 92%
“…Biochar amendment increased the relative abundance of Micromonospora, which is known to have plant growth-promoting traits including nitrogen fixation and the inhibition of plant pathogens (Li et al, 2022); our results were in agreement with this study, for being the dominant genus in 30 mesh. Micromonospora not only presented higher relative abundance in biochar and BOF treatments compared with CK but also showed a strong positive correlation with AN, AP, and K. Bacillus spp.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that biochar can effectively improve the physicochemical properties of soil and cause alterations in the soil microbial community because of the special structure and properties of biochar (Lucheta et al, 2016). Bacterial diversity increased after the soil was amended with biochar for half a year, which was consistent with previous studies (Li et al, 2022). Additionally, it was observed that the abundance of bacteria in soil was increased by the application of chemical fertilizers, particularly F and FM.…”
Section: Resultssupporting
confidence: 92%
“…This result is consistent with the findings of Deng et al, who reported enhanced Micromonospora growth under the biochar and microcapsule treatment of phenanthrene polluted soil [63]. According to Li et al, Micromonospora has plant-growth-promoting traits, including nitrogen fixation and the inhibition of plant pathogens, therefore, it may aid B_BOF-and BOF-induced plant growth [64]. Gaiella and norank_o_Gaiellales are both Actinobacteria, which promote plant growth by increasing the nutrient availability and assimilating and enriching the beneficial bacteria.…”
Section: Discussionsupporting
confidence: 92%